Analisis Implementasi Sistem Informasi Manajemen Pendidikan Berbasis Digital di SDN 4 Sukomulyo - Nimatul Khoeriyah; Ali Muhdi (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The rapid development of information technology has encouraged educational institutions to implement Management Information Systems (MIS) to improve the quality of school administration services. This study aims to describe the planning and implementation of MIS at SDN 4 Sukomulyo, identify supporting and inhibiting factors, and evaluate the impact on school management effectiveness. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, teachers, administrative staff, and school operators, as well as participatory observation and document review. Data validity was ensured through source, method, and time triangulation. The results show that SDN 4 Sukomulyo has implemented several MIS components, primarily DAPODIK and e-Raport systems. Key supporting factors include active principal support, internet network availability, and teacher motivation. The main inhibiting factors are limited hardware, uneven digital literacy among staff, and unstable internet connection. MIS implementation has contributed to increased administrative efficiency, improved data accuracy, and greater transparency of school information to stakeholders.